2013
DOI: 10.2134/agronj2012.0352
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake, Partitioning, and Remobilization in Modern, Transgenic Insect‐Protected Maize Hybrids

Abstract: Modern maize (Zea mays L.) hybrids coupled with improved agronomic practices may have influenced the accumulation and partitioning of nutrient uptake since the last comprehensive studies were published. The objective of this study was to investigate nutrient uptake and partitioning among elite commercial germplasm with transgenic insect protection grown under modern management practices. Plants were sampled at six growth stages and divided into four fractions for nutrient determination. Total nutrients require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
304
8
39

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(379 citation statements)
references
References 35 publications
28
304
8
39
Order By: Relevance
“…However, S inputs have decreased in many regions over the last decades because of a decrease in atmospheric S deposition due to stricter pollution control and because of a shift towards high-analysis S-free fertilizers. On the other hand, crop removal of S in new high-yielding varieties has increased (Bender et al 2013). As a result, S deficiency has become more frequent in many agricultural areas (Scherer 2001;Haneklaus et al 2008), resulting in an increased need for S fertilization (Ceccotti 1996).…”
mentioning
confidence: 99%
“…However, S inputs have decreased in many regions over the last decades because of a decrease in atmospheric S deposition due to stricter pollution control and because of a shift towards high-analysis S-free fertilizers. On the other hand, crop removal of S in new high-yielding varieties has increased (Bender et al 2013). As a result, S deficiency has become more frequent in many agricultural areas (Scherer 2001;Haneklaus et al 2008), resulting in an increased need for S fertilization (Ceccotti 1996).…”
mentioning
confidence: 99%
“…Similarly, Carsky and Reid (1990) analyzed whole-plant tissue Zn in 3-to 6-week-old plants and observed that tissue Zn concentration explained only 21% of the variability in grain yields. Maize Zn content at the eighth leaf stage represents less than 10% of the total Zn uptake at maturity (Bender et al, 2013), which explains the relative weakness of tissue testing as a Zn diagnostic tool. In another study that related tissue Zn concentration in 6-week-old plants to its available supply, Hiatt and Massey (1958) observed that plants showing severe deficiency symptoms were stunted and had a relatively high Zn concentration, while lowest tissue Zn concentrations occurred when maize deficiency symptoms were mild and plants grew more.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc removal with the maize grain and harvest index is the largest among all micronutrients (Bender et al, 2013). Bender et al (2013) reported that 308 g ha −1 were removed with the grain and a 62% harvest index on average for six hybrids that yielded 12,000 kg ha −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of nitrogen uptake in this particular stage is driven by balanced uptake of other nutrients, such as potassium, phosphorus, and magnesium [15][16][17][18][19][20]. In modern staygreen varieties, the amount of nitrogen taken up by maize at the beginning of flowering constitutes around 50% of its final uptake [4,5,21]. The amount of mineral nitrogen taken up by maize during the grain-filling period depends to a great extent, irrespective of nutrient supply, on crop capacity to its utilization [22][23][24].…”
Section: Introductionmentioning
confidence: 99%